The Cambridge Handbook of Policing in the United States 2019
DOI: 10.1017/9781108354721.020
|View full text |Cite
|
Sign up to set email alerts
|

Police and the Criminalization of LGBT People

Abstract: This chapter uses the acronym "LGBT" to refer to lesbian, gay, bisexual, and transgender people. There are some instances where the acronym "LGBTQ" is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…However, prior research documents that law enforcement and antiviolence programs and services may be unprepared to effectively serve LGBT victims and address the full scope of their needs [ 40 , 41 ]. In addition, the extant research on bias crime victim responses have demonstrated significant gaps and inadequate services that can further victimize people a they seek assistance [ 42 ], and very few countries offer trained specialist support for the unique needs of victims of hate crimes [ 43 ].…”
Section: Public Policy and Broader Implicationsmentioning
confidence: 99%
“…However, prior research documents that law enforcement and antiviolence programs and services may be unprepared to effectively serve LGBT victims and address the full scope of their needs [ 40 , 41 ]. In addition, the extant research on bias crime victim responses have demonstrated significant gaps and inadequate services that can further victimize people a they seek assistance [ 42 ], and very few countries offer trained specialist support for the unique needs of victims of hate crimes [ 43 ].…”
Section: Public Policy and Broader Implicationsmentioning
confidence: 99%
“…Since the 20th century, homophobic violence (HV) has been a relevant issue for academicians, society, and politics (Goldberg et al, 2019; International Lesbian, Gay, Bisexual, Trans and Intersex Association [ILGA], 2019). At present, greater acceptance is observed toward homosexuality than decades ago (Goldberg et al, 2019). This is shown by more positive attitudes toward homosexuals in some countries of Europe and America (Barrientos, 2015; Donaldson et al, 2017).…”
Section: Violence and Bodymentioning
confidence: 99%
“…Queer relationships raise similar concerns—I return to this in the first case study. The fact that queer and trans relations are often raced and classed calls for an intersectional approach particularly as it relates to passing institutional judgment on specific relationships (Goldberg et al, 2019; Mogul et al, 2011).…”
Section: An Alternative Approachmentioning
confidence: 99%